HIERARCHY, AMATEURISM AND SOCCER: TRADITIONAL FACES OF CAXIAS ESPORTE CLUBE (Fiep Bulletin - online, 2014)
The objective of this study is to identify the administrative differences of Caxias Esporte Clube, an amateur soccer team from Espírito Santo´s scenario. The problem is to reveal the reasons that took the team to prevent from supporting soccer soon after the period when it conquered the championship among the professional capixaba´s teams in 1970. This study revealed that CEC has two facets which are characteristics of amateurism still found today in Brazilian soccer teams: Leaders' ethnocentric hierarchy and amateur structure of managing soccer rules.
Keywords: Soccer; Hierarchy; Amateur; Professional